USAHA EKONOMI KREATIF BERBASIS KEARIFAN LOKAL DAN KORELASINYA DENGAN KESETARAAN GENDER DI KOTA MERAUKE - Ismail; Parman; Ratu bulkis ramli (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The creative economy sector is one of the business fields for local communities, besides that it can also be a job opportunity for women, especially housewives. Merauke City is famous for its various local wisdom so that it can be a business opportunity for creative economy actors. For this reason, this study aims to identify forms of creative economy businesses based on local wisdom and their relevance to gender equality in the community in the city of Merauke. The approach used in this study is qualitative descriptive. While the techniques used are observation, interviews, and documentation. While the data analysis techniques used are data reduction, data presentation, and conclusions. Based on the results of the research conducted, several forms of creative economy businesses were found carried out by the community in the city of Merauke, including; Noken making, rattan weaving crafts, mebel, making wallets and bags from crocodile skin, and crafts from agarwood. The income generated from creative businesses based on local wisdom varies and greatly helps the family's economy. Meanwhile, women's involvement in the creative economy of the community is still in the business of making noken and crocodile skin craftsmen. However, these can be small steps taken by women in terms of involving themselves in the public sphere, especially in the aspect of earning work.